2017
DOI: 10.1186/s40635-017-0130-9
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular superoxide dismutase is necessary to maintain renal blood flow during sepsis development

Abstract: BackgroundExtracellular superoxide dismutase (ECSOD) protects nitric oxide (NO) bioavailability by decreasing superoxide levels and preventing peroxynitrite generation, which is important in maintaining renal blood flow and in preventing acute kidney injury. However, the profile of ECSOD expression after sepsis is not fully understood. Therefore, we intended to evaluate the content and gene expression of superoxide dismutase (SOD) isoforms in the renal artery and their relation to renal blood flow.MethodsSepsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…These findings strongly support that enhanced EcSOD expression from skeletal muscle or other tissues/organ, which can be redistributed to the lung tissue, could be a viable preventative/therapeutic measures in reducing the risk and severity of ALI/ARDS. Considering the current outbreak of the 2019 Novel Corona virus infection (COVID- 19), which is an infectious disease that leads to progressive ALI/ARDS in many patients (6,103,107,113), it is conceivable that regular exercise might be effective in preventing while EcSOD gene/protein therapy might be effective in treating ALI/ARDS under the condition of COVID-19 infection.…”
Section: Adenovirus-mediated Overexpression Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings strongly support that enhanced EcSOD expression from skeletal muscle or other tissues/organ, which can be redistributed to the lung tissue, could be a viable preventative/therapeutic measures in reducing the risk and severity of ALI/ARDS. Considering the current outbreak of the 2019 Novel Corona virus infection (COVID- 19), which is an infectious disease that leads to progressive ALI/ARDS in many patients (6,103,107,113), it is conceivable that regular exercise might be effective in preventing while EcSOD gene/protein therapy might be effective in treating ALI/ARDS under the condition of COVID-19 infection.…”
Section: Adenovirus-mediated Overexpression Ofmentioning
confidence: 99%
“…Acute kidney injury (AKI). Mouse models in which the EcSOD gene is mutated or SOD inhibitors are used suggest protective role of EcSOD against renal injury (19,45,95,104).…”
Section: Copdmentioning
confidence: 99%
See 1 more Smart Citation
“…Sepsis is a complex syndrome characterized by an imbalance between proinflammatory and anti-inflammatory responses to pathogens [ 9 ]. During the development of sepsis, a large number of reactive oxygen species (ROS) and nitric oxide (NO) will be produced [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…One of the primary antioxidants responsible for counteracting oxidative stress is superoxide dismutase (SOD). Constantino et al [ 9 ] stated that SOD is one of the natural antioxidant enzymes found in body cells due to several factors. As you grow older, this antioxidant activity can decrease so that antioxidants from outside the body are needed, one of which is Glisodin, a synthetic SOD.…”
Section: Introductionmentioning
confidence: 99%